Are seat belt restraints as effective in school age children as in adults? A prospective crash study. Issue 7346 (11th May 2002) - Halman, Stephen I; Chipman, Mary; Parkin, Patricia C; Wright, James G
Abstract: Objective: To study effectiveness of seat belts for protecting school age children in road vehicle crashes. Design: Crash examinations by trained investigators. Setting: Ten Canadian university based crash investigation centres. Subjects: 470 children aged 4-14 years, with 168 selected for detailed analysis, and 1301 adults. Main outcomes measures: Use of seat belts by vehicle occupants; severity of injury adjusted for age and crash severity. Results: Overall, 40% (189/470) of children were unbelted. Of the 335 children in cars driven by belted adults, 73 (22%) were unbelted. The odds of sustaining fatal or moderately severe injury (injury severity score ≥4) for children in the front passenger seat was more than nine times higher for unbelted children than for belted ones (odds ratio 9.8 (95% confidence interval 2.4 to 39.4)) and for those in the rear left seat was more than two times higher for unbelted than for belted children (2.6 (1.1 to 5.9)). The protection afforded by seat belts compared favourably with the results for adults in the same seat positions (odds ratios for unbelted v belted adults of 2.4 and 2.7 for front and rear seat passengers respectively). Conclusions: Seat belts helped to protect school age children from injury in road vehicle crashes. However, 40% of children were unbelted. Despite standard seat belts being designed for adults, school age children were at least as well protected as adults.